Penerapan Model Promosi Kesehatan Terhadap Kemampuan Ibu Dalam Pemenuhan Zat Gizi Pada Anak Stunting - Hastuti, Apriyani Puji; Suprawoto, Dina Nurpita; Roesardhyati, Ratna; Fani, Rif'atul (Journal of Islamic Medicine, 2023)
Background: Health promotion regarding the provision of nutrition to children who experience stunting is closely related to the role of mothers in using their knowledge, belief and abilities in improving nutrition and fulfilling adequate nutrition in children. Objective: to analyze the ability of mothers to fulfill nutrition in children aged 6-24 months who are stunted. Method: the research design used a quasy-experiment with a pre-test post-test control group design approach with a sample size of 114 mothers with stunted children who were taken using a random technique with cluster sampling. The independent variable in this study is health promotion based on the health promotion model and the dependent variable is the mother's ability to fulfill nutrition in children aged 6-24 months who are stunted. The research instrument used a questionnaire for each variable. Data analysis in this study is the Wilcoxon Signed Rank Test and Mann Whitney. Result The ability of mothers to fulfill nutrition in children aged 6-24 months who experience stunting with indicators of continuity of breastfeeding 74.636.85 (p-value = 0.000), food preparation and processing 95.105.35 (p-value = 0.000), complementary feeding 87.316.89 (p-value=0.000) and responsive feeding 87.927.27 (p-value=0.000) and there is a difference between the treatment group and the control group regarding the mother's ability to fulfillment of nutrition in stunted children with a p-value of 0.000 Conclusion: there is a significant difference in the ability of mothers to fulfill nutrition in stunted children